Hybrid ZnSe‐SnSe2 Nanoparticles Embedded in N‐doped Carbon Nanocube Heterostructures with Enhanced and Ultra‐stable Lithium‐Storage Performance. Issue 24 (2nd September 2021) - Yu, Litao; Kim, Kyung Su; Saeed, Ghuzanfar; Kang, Jun; Kim, Kwang Ho
Abstract: Bimetallic selenide composites with multiple valence transitions and high theoretical capacities have attracted great attention as lithium‐ion‐battery anodes, but their rapid capacity fading and scarce research limit their development. Herein, novel hybrid ZnSe‐SnSe2 nanoparticles embedded in N‐doped carbon nanocubes (ZSS⊂NCNs) are synthesized by a facile nucleation assembly, carbon coating, and in situ selenation route. The obtained uniform ZSS⊂NCN materials exhibit high surface area, N‐doping carbon shell, extra inner void space, and excellent resilient mechanism nanostructure, which provide amounts of active sites, outstanding electrochemical kinetics, and buffer the volume expansion in the conversion and alloy/dealloy processes. For lithium‐ion‐battery half‐cells, the uniform ZSS⊂NCN materials display a high initial coulombic efficiency of 81.9 %, an increased capacity of 846.6 mA h g −1 at 0.2 A g −1 after 100 cycles, and an excellent rate capability (414.1 mA h g −1 at 5 A g −1 ). When assembled with a LiMn2 O4 cathode, the ZSS⊂NCNs//LiMn2 O4 full cells also present excellent electrochemical properties. Ex situ XRD analyses at different potentials in the lithiation/delithiation processes confirm a polymorphic phase transformation in the ZSS⊂NCNs. The synthesized ZSS⊂NCN enriched bimetallic selenide composites and the facile synthesis route provide a strategy for other bimetallic selenides, sulfide or phosphide composites with stable nanostructure to be utilized in energy storage. Abstract : Hybrid ZnSe‐SnSe2 nanoparticles embedded in N‐doped carbon nanocubes (ZSS⊂NCNs) are synthesized by a facile nucleation assembly, carbon coating, and in situ selenation route. For lithium‐ion‐battery half‐cells, the uniform ZSS⊂NCN materials display a high initial coulombic efficiency of 81.9 %, an increased capacity of 846.6 mA h g −1 at 0.2 A g −1 after 100 cycles, and an excellent rate capability (414.1 mA h g −1 at 5 A g −1 ). The ZSS⊂NCNs//LiMn2 O4 full cells also present excellent electrochemical properties.